On estimates of regression coefficients in multivariate case - Gylys, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Гилис. Об оценках коэффициентов регрессии в многомерном случае R. Gylys. Apie regresijos koeficientų įvertinimus daugiamačiu atveju